Integrated Project Eureka Intervention: Effect on the Discourse Skills in English Among Grade 11 Students - Llorca, Alma Gay; Blancia, Garry Vanz; Villanueva, Emelyn (Romblon State University Research Journal, 2022)
This quasi-experimental study was conducted to determine the effect of Integrated Project Eureka Intervention (IPEI) on the Discourse Skills (DS) in English of Grade-11 Humanities and Social Sciences (HUMSS) students at Odiongan National High School. Two intact HUMSS classes were selected and assigned each to control and experimental groups, respectively. In determining the DS, a 20-item standardized assessment for communicative/discourse test was adapted from University of Louisville. T-test for independent samples was used to compare the mean pre-test scores in DS of the experimental and control classes. Analysis of Covariance was used to compare the post-test mean scores in DST between the two classes, using DST mean pre-test scores as covariates. Results of the investigation revealed that the IPEI was effective (ηp2 = 0.4) in improving the discourse skills of HUMSS students. A longer period of experimentation to fully ascertain the dosage of the intervention and to test the intervention to different strands in the senior high school program are recommended.